Lecturer's Perception of Google Translate as an Academic Tool: Appraisal Analysis - Fahmi Gunawan; Aini Khairunnisa (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
Although research on Google Translate (GT) has been widely documented, there is a dearth of research examining Arabic lecturers' perspectives on GT from an appraisal point of view. This empirical research discusses how Arabic lecturers perceive the usage of GT as a tool for academics. The participants come from ten different Arabic language lecturers. Surveys and in-depth interviews were undertaken to gather data. The appraisal theory proposed by Martin and White (2005) was used for data analysis. The findings demonstrate how lecturers' perceptions of the usage of GT can be divided into four categories happiness and unhappiness, satisfied and unsatisfied. GT is popular among lecturers since it is simple to use, accessible, affordable, provides voice recording functions, and requires little language proficiency. Meanwhile, their unhappiness with GT arises because they find it challenging to grasp due to its literal translation, ambiguity, and poor source language input. Satisfaction with the lecturers arises from GT's assistance with their tasks, whereas dissatisfaction results from GT's inability to translate cultural terms. To this end, discussion and implications are discussed at the end of the study.